2017
DOI: 10.1002/2016jd025933
|View full text |Cite
|
Sign up to set email alerts
|

Electrical discharges in the overshooting tops of thunderstorms

Abstract: Previous studies have found that the vertical distribution of sources of very high frequency (VHF) signals from discharges mapped by Lightning Mapping Arrays typically have a secondary maximum in a storm's overshooting top. Low rates of these sources tend to occur continually throughout the lifetime of the overshooting top (OT), rather than sources occurring in the episodic distinct flashes observed at lower altitudes. This study examines the evolution of the VHF OT signature (VHF OT, defined here as a sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 99 publications
(221 reference statements)
3
33
1
Order By: Relevance
“…While the bulk of the lightning occurred below 12 km altitude, the storm also featured significant VHF source activity above 15 km, within the OT (Figure 7a). OT‐based electrical activity has been noted before in the LMA literature (e.g., MacGorman et al, 2017), and similar to those studies, the activity tended to consist of continual low rates of sources without well‐defined channels. This may be related to the size of the physical discharges being small relative to the expected spatial resolution of the LMA at ranges like these (~1 km; Thomas et al, 2004).…”
Section: Case Study Analysis: 11 December 2018supporting
confidence: 76%
“…While the bulk of the lightning occurred below 12 km altitude, the storm also featured significant VHF source activity above 15 km, within the OT (Figure 7a). OT‐based electrical activity has been noted before in the LMA literature (e.g., MacGorman et al, 2017), and similar to those studies, the activity tended to consist of continual low rates of sources without well‐defined channels. This may be related to the size of the physical discharges being small relative to the expected spatial resolution of the LMA at ranges like these (~1 km; Thomas et al, 2004).…”
Section: Case Study Analysis: 11 December 2018supporting
confidence: 76%
“…However, accounting for such lags may reduce the error associated with flash rate parameterizations. Finally, this study did not explicitly consider over-shooting top (OT) electrical discharges [89] or downward positive intracloud lightning (+IC) [90], which both occur at high altitudes and temperatures colder than the mixed-phase zone microphysical and kinematic parameters emphasized in this study. OT electrical discharges would be eliminated by the source-to-flash clustering methods used in this study and not included in our flash rate totals.…”
Section: Statistical Errorsmentioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres, 124, 6982-6998. https://doi.org/ 10. 1029/2018JD029907 et al, 2012 and discharges in the overshooting tops (e.g., MacGorman et al, 2017), we can find few reports of full-fledged IC flashes initiated at high altitudes such as above 12 km.…”
Section: 1029/2018jd029907mentioning
confidence: 83%
“…Calhoun et al () reported that the majority of lightning flashes in a supercell were initiated near altitudes of 10 to 11 km and noted that such supercell was “unusual” compared to other storms. In fact, other than some special types of lightning discharges that do not comprise clear leader channels, such as narrow bipolar events (NBEs; e.g., Smith et al, ; Wu et al, ) and discharges in the overshooting tops (e.g., MacGorman et al, ), we can find few reports of full‐fledged IC flashes initiated at high altitudes such as above 12 km.…”
Section: Introductionmentioning
confidence: 99%